Nitrogen removal characteristics of indigenous aerobic denitrifiers and changes in the microbial community of a reservoir enclosure system via in situ oxygen enhancement using water lifting and aeration technology. (August 2016) - Zhou, Shilei; Huang, Tinglin; Ngo, Huu Hao; Zhang, Haihan; Liu, Fei; Zeng, Mingzheng; Shi, Jianchao; Qiu, Xiaopeng
Highlights: The indigenous aerobic denitrifiers were enhanced in situ . The enhanced system performed very well in terms of nitrogen removal and the inhibition of Fe, Mn and P pollutants. The N-functional bacteria were obviously increased via in situ oxygen enhanced. Nitrogen source, Fe, Mn, DO were the most important factors affecting the bacterial community function and composition. Abstract: Indigenous aerobic denitrifiers of a reservoir system were enhanced in situ by water lifting and aeration technology. Nitrogen removal characteristics and changes in the bacterial community were investigated. Results from a 30-day experiment showed that the TN in the enhanced water system decreased from 1.08–2.02 to 0.75–0.91 mg/L and that TN removal rates varied between 21.74% and 52.54% without nitrite accumulation, and TN removal rate of surface sediments reached 41.37 ± 1.55%. The densities of aerobic denitrifiers in the enhanced system increased. Furthermore, the enhanced system showed a clear inhibition of Fe, Mn, and P performances. Community analysis using Miseq showed that diversity was higher in the in situ oxygen enhanced system than in the control system. In addition, the microbial composition was significantly different between systems. It can be concluded that in situ enhancement of indigenous aerobic denitrifiers is very effective in removing nitrogen from water reservoir systems.